ANALISIS PERBANDINGAN BENTUK DAN MAKNA VERBA REDUPLIKASI DALAM BAHASA MANDARIN DAN BAHASA INDONESIA - Nurlaili, Indria Pradita; Veronica, Tjen; Khiong, Bun Yan (Universitas Tanjungpura, 2024)
Both Chinese and Indonesian have their own types of word reduplication, and verb reduplication is one of them. This study aims to describe the form, meaning of verb reduplication in Chinese and Indonesian, as well as to describe the similarities and differences of verb reduplication in these two languages. The research used in this paper is literature research method. Verbs in Chinese and Indonesian also have important grammatical characteristics. The results obtained are from 7 forms of Chinese verb reduplication, the AA form has the largest percentage of the data and shows the meaning of short time experienced by the action. While Indonesian verb reduplication from 5 forms with the largest percentage of the data contained in the form of partial reduplication and shows the meaning of actions that have intensity. The similarity between Chinese and Indonesian verb reduplication is that both languages have a complete form of reduplication. The difference between the two languages is that Indonesian has a hyphen (-) which indicates that the word is a reduplication, while in Chinese there is none. There are some forms of affixes in Indonesian, but not in Chinese. Chinese verb reduplication has the means